2016
DOI: 10.1007/s10103-016-1868-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical periodontal therapy with/without diode laser modulates metabolic control of type 2 diabetics with periodontitis: a randomized clinical trial

Abstract: In order to evaluate whether nonsurgical periodontal treatment with/without diode laser (DL) decontamination improves clinical parameters, the levels of IL-1β, IL-6, IL-8, intercellular adhesion molecule (ICAM), and vascular cell adhesion molecule (VCAM) in gingival crevicular fluid and metabolic control (HbA1c) in chronic periodontitis (CP) patients with diabetes mellitus type 2 (DM2). Sixty patients with DM2 and CP were randomly assigned into two groups to receive scaling and root planing (SRP, n = 30) or SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 57 publications
5
24
0
1
Order By: Relevance
“…30,31 This is in contradiction to a recent study by Koçak and Sağlam which showed SRP+ Diode laser group showed statistically significant improvement in glycemic control (HbA1c) than in SRP group in patients with DM2 and CP. 32 The present study showed improvement in all clinical parameters (PI, GI, PD, CAL) from baseline to 3 months in SRP and SRP+LANAP group which was statistically significant. The value of plaque index reduced from 2.31 at baseline to 1.56 at 3 months in control and from 2.45 to 1.26 in the test group.…”
Section: Hba1c(%)supporting
confidence: 64%
“…30,31 This is in contradiction to a recent study by Koçak and Sağlam which showed SRP+ Diode laser group showed statistically significant improvement in glycemic control (HbA1c) than in SRP group in patients with DM2 and CP. 32 The present study showed improvement in all clinical parameters (PI, GI, PD, CAL) from baseline to 3 months in SRP and SRP+LANAP group which was statistically significant. The value of plaque index reduced from 2.31 at baseline to 1.56 at 3 months in control and from 2.45 to 1.26 in the test group.…”
Section: Hba1c(%)supporting
confidence: 64%
“…Hence, considerable attention was paid in drawing an association between periodontitis and certain inflammatory cytokines, such as interleukin-1 (IL-1), tumor necrosis factor-α (TNF-α), and matrix metalloproteinase-8 (MMP-8). Moreover, the presence of such inflammatory cytokines has been proved to be altered in serum, gingival crevicular fluid, and saliva in patients with periodontitis [811]. …”
Section: Introductionmentioning
confidence: 99%
“…For the second time in the literature, this study investigated the effects of DL application in addition to SRP on systemic inflammatory response (CRP) and metabolic control of DM (HbA 1c level) in poorly controlled DM patients . Findings of this study indicate that both SRP and SRP+DL application provided positive contributions to periodontal and systemic conditions in patients with T2DM.…”
Section: Discussionmentioning
confidence: 91%
“…In the literature, there is only one study evaluating the effects of DL, which has been applied in contact mode in addition to scaling and root planing (SRP). This study reported SRP+DL reduced haemoglobin A 1c (HbA 1c ) levels more significantly compared to SRP in T2DM patients …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation